2022
DOI: 10.1111/bjet.13190
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement in online learning in Latin American higher education during the COVID‐19 pandemic: A systematic review

Abstract: The COVID-19 pandemic has forced higher education institutions to implement online learning activities based on virtual platforms, allowing little time to prepare and train faculty members to familiarize students with digital technologies. While previous studies have looked at how students engaged with digital technologies in their learning activities, the characteristics of the student engagement in online learning remain underexplored. Therefore, a systematic review of the literature on student engagement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(152 citation statements)
references
References 63 publications
4
138
1
9
Order By: Relevance
“…The positive association between prior learning experiences and students' evaluation of and satisfaction with online education is in line with the findings of other studies conducted during the pandemic [95][96][97]. Studies have also shown the positive association between students' self-rated readiness for online learning and their satisfaction with ERL [95,98,99].…”
Section: Students' Technology Background and Self-rated Preparedness ...supporting
confidence: 88%
See 2 more Smart Citations
“…The positive association between prior learning experiences and students' evaluation of and satisfaction with online education is in line with the findings of other studies conducted during the pandemic [95][96][97]. Studies have also shown the positive association between students' self-rated readiness for online learning and their satisfaction with ERL [95,98,99].…”
Section: Students' Technology Background and Self-rated Preparedness ...supporting
confidence: 88%
“…Forming of online peer support groups: One of the issues affecting emergency remote learning witnessed in our study and the literature is the stress and isolation due to the lack of face-to-face contact [99]. To combat this, students should be encouraged to develop and utilize online peer support networks.…”
Section: Student Development and Supportmentioning
confidence: 98%
See 1 more Smart Citation
“…Forth, according to Janosz (2012), engagement can be considered in the contexts of different nature: (a) the context of specific learning activities, (b) the classroom context, in which the students have to manage not only academic but also socioemotional learning, and (c) the school context, which can be more or less learningoriented . To these factors, it should be added a fourth one: whether the teaching context is face-to-face, distance, or virtual (Martin et al, 2022;Salas-Pilco et al, 2022). Therefore, the determinants and outcomes of engagement at each level can be different.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition to the seven original research papers, the special section includes two review papers. Salas‐Pilco et al ( 2022 ) conduct a systematic review of literature on online student engagement in Latin American higher education. Student engagement is examined in three dimensions: behavioural, cognitive and affective.…”
Section: Holistic Views Of Ert In a Latin American And A Global Contextmentioning
confidence: 99%